2021
DOI: 10.17582/journal.aavs/2021/9.8.1123.1134
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Dietary Pomegranate Seeds Powder Supplementation against Oxidative Stress of Organochlorine Pesticides Residues in Growing Rabbits

Abstract: The objective of this work was to evaluate the pomegranate seeds powder (PSP) as an effective antioxidant in growing rabbit's diets to alleviate the adverse effects of organochlorine pesticides residues (OCPs) on growth performance, antioxidant status and physiological parameters of growing rabbits. A total of 120 unsexed weaned V-Line male rabbits (4 weeks of age) were assigned at random to five experimental groups. The control group was fed a diet free of PSP. The negative control was fed a diet free of PSP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Consequently, a reduction in MDA concentration is associated with increased antioxidant enzymatic activity due to PSE supplementation. This finding is corroborated by the ideas of Hassan et al [54], who suggested an increase in SOD, GSH, and CAT enzymes activity, and a decrease in MDA content in the case of a rabbit's diet supplemented by PSE. 2021) stated that the administration of PSE antagonizes the effects of AFB1 as it contains many biologically active compounds such as minerals (Zn and Se), vitamins (C and E), and (total phenols and flavonoids) [54].…”
Section: Antioxidant Statussupporting
confidence: 84%
See 2 more Smart Citations
“…Consequently, a reduction in MDA concentration is associated with increased antioxidant enzymatic activity due to PSE supplementation. This finding is corroborated by the ideas of Hassan et al [54], who suggested an increase in SOD, GSH, and CAT enzymes activity, and a decrease in MDA content in the case of a rabbit's diet supplemented by PSE. 2021) stated that the administration of PSE antagonizes the effects of AFB1 as it contains many biologically active compounds such as minerals (Zn and Se), vitamins (C and E), and (total phenols and flavonoids) [54].…”
Section: Antioxidant Statussupporting
confidence: 84%
“…This finding is corroborated by the ideas of Hassan et al [54], who suggested an increase in SOD, GSH, and CAT enzymes activity, and a decrease in MDA content in the case of a rabbit's diet supplemented by PSE. 2021) stated that the administration of PSE antagonizes the effects of AFB1 as it contains many biologically active compounds such as minerals (Zn and Se), vitamins (C and E), and (total phenols and flavonoids) [54]. The identified vitamins, including vitamins (C, E, and A) in the peels and seeds of the pomegranate plant, are well-known for their powerful antioxidant capabilities [55].…”
Section: Antioxidant Statussupporting
confidence: 84%
See 1 more Smart Citation